Topography of the three late mRNA's of polyoma virus which encode the virion proteins. - Kamen, R (1980)
The three cytoplasmic polyadenylated mRNA's which separately encode the three capsid proteins (VP1, VP2, and VP3) of polyoma virus were mapped on the viral genome by one- and two-dimensional gel electrophoreses of nuclease S1-resistant RNA-DNA hybrids. The mRNA's, which we designated mVP1, mVP2, and mVP3 to indicate the coding functions deduced from the cosedimentation of the RNAs and the messenger activities, comprise an overlapping set of 3'-coterminal molecules which also share a heterogeneous family of noncoding 5'-terminal regions (Flavell et al., Cell 16:357--371, 1979; Legon et al., Cell 16:373--388, 1979). The three species differ in the length of the 3' colinear coding region which is spliced to the 5' leader sequences. The common polyadenylated 3' end maps at map unit 25.3. The 5' ends of the colinear bodies of mVP1, mVP3, and mVP2 map at 48.5, 59.5, and 66.5 map units, respectively. An examination of the polyoma virus DNA sequence (Arrand et al., J. Virol. 33:606--618, 1980) in the vicinities of splicing sites approximated by the S1 gel mapping data for sequences common to the ends of known intervening sequences allowed prediction of the precise splice points in polyoma virus late mRNA's. In all three cases, the leader sequences are joined to the mRNA bodies at least 48 nucleotides before the translational initiation codon used in each particular messenger. The start signal which functions in each mRNA is the first AUG (or GUG) triplet after the splice junction.